Implementasi Model Prototyping dan Framework Laravel dalam pengembangan Sistem Informasi Kesekretariatan - Muh Azikin Sofyan; Aminuddin Bakry; Jumadi M Parenreng (Progressive Information, Security, Computer, and Embedded System, 2023)
This study aims to determine the results of web-based JTIK FT UNM secretarial information system development and to test the quality of the system using the ISO 25010 standard. This research is research and development or Research and Development (R&D). This study uses the prototyping development model which is a development method of the system development life cycles (SDLC). Data was collected using interviews, observation, documentation and questionnaires. The results obtained in the form of web-based JTIK FT UNM secretarial information system development results with the results of testing using the ISO 25010 standard on functionality suitability characteristics are worth 1 (very good), on reliability characteristics obtained a reliability level of 100% (Fulfilling), on performance efficiency characteristics obtained a performance value of 97.4% (Grade A) Structure of 88.2% (Grade A) and Fully load time of 1.36 (acceptable), on Usability characteristics obtained a feasibility percentage of 93.2% (very feasible), on Security characteristics found no viruses and malware on the information system, on the compatibility characteristics it is worth 1 (very good), on the portability characteristics it is 1 (very good), and maintainability meets the standard 3 aspects of assessment. Based on the results of this study, it can be concluded that the JTIK FT UNM secretarial information system that has been created can function properly and is feasible to use.